Strengthening the “Misi Keugaharian” as A Faith and Cultural Responsibility towards The Environment for The Toraja Church Women's Fellowship (PWGT) of the Bua Tallulolo Kesu' South Toraja - Ruadjanna Tangirerung, Johana; Ammay Bungaran, Stephanus; Rejeki, Bedsy; Jona Yumarto, Ivanka; Tangkelayu, Rhuny (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2024)
Environmental crises and degradation have become prominent issues in the past decade, exacerbated by misinterpretations of religious values and local wisdom. Rather than acting as stewards of the environment, humans have contributed to ecological problems. This Community Service Program collaborates with PWGT Bua Tallulolo, who have been identified as lacking the resources and capacity to address the environmental crisis effectively. The primary goal of this Community Service Program is to provide guidance and support in understanding the church's mission and its relationship with religious attitudes towards environmental stewardship through the